Quinolinic acid, a kynurenine/tryptophan pathway metabolite, associates with impaired cognitive test performance in systemic lupus erythematosus - Anderson, Erik W; Fishbein, Joanna; Hong, Joseph; Roeser, Julien; Furie, Richard A; Aranow, Cynthia; Volpe, Bruce T; Diamond, Betty; Mackay, Meggan (Lupus science & medicine, 2021)
ObjectivesInterferon-alpha, an important contributor to SLE pathogenesis, induces the enzyme indoleamine 2,3-dioxygenase in the kynurenine/tryptophan (KYN/TRP) pathway. This leads to a potentially neurotoxic imbalance in the KYN/TRP pathway metabolites, quinolinic acid (QA), an N-methyl D-aspartate glutamatergic receptor (NMDAR) agonist, and kynurenic acid (KA), an NMDAR antagonist. We determined whether QA/KA ratios associate with cognitive dysfunction (CD) and depression in SLE.MethodsThis cross-sectional study included 74 subjects with SLE and 74 healthy control (HC) subjects; all without history of neuropsychiatric disorders. Serum metabolite levels (KYN, TRP, QA, KA) were measured concurrently with assessments of cognition (Automated Neuropsychological Assessment Metrics (ANAM), 2×2 array), mood and pain, and compared between SLE and HC. Multivariable modelling in SLE was used to evaluate associations of metabolites with cognitive performance and depression.ResultsSerum KYN/TRP and QA/KA ratios were elevated in SLE versus HC (p<0.0001). SLE performed worse than HC on four of five ANAM tests (all p≤0.02) and the 2×2 array (p<0.01), and had higher depression scores (p<0.01). In SLE, elevated QA/KA ratios correlated with poor performance on Match to Sample (MTS), a working memory and visuospatial processing task (p<0.05). Subjects with SLE with elevated QA/KA ratios also had slightly higher odds of depression, but this did not reach significance (p=0.09). Multivariable modelling in SLE confirmed an association between QA/KA ratios and poor MTS performance when considering potentially confounding factors (p<0.05).ConclusionsElevated serum KYN/TRP and QA/KA ratios confirm KYN/TRP pathway activation in SLE. The novel association between increased QA/KA ratios and poor cognitive performance supports further study of this pathway as a potential biomarker or therapeutic target for SLE-mediated CD.